Frequency Characteristics of the Electrical Fields of the Cylindrical System of the Piezoceramic Radiators with the Baffle in the Inner Cavity - A.G. Leiko; Y.I. Starovoit (Журнал нано- та електронної фізики)
Using the connected fields method in multi connected areas equations for calculating electrical fields of the cylindrical piezoceramic radiators as a part of the cylindrical system with the baffle in the inner cavity were obtained. Analysis of the results of the numerical experiments allow us to determine some special features in the electrical fields, that influence on the energetical efficiency of the radiating systems. Physical explanations of this special features are given.